Tingkat Motivasi Petani dalam Budidaya Jambu Air Citra (Syzygium aqueum) di Dusun Sumberagung Kecamatan Tegalsari Kabupaten Banyuwangi - Erik Elnanta; Nurul Dwi Novikarumsari; Aryo Fajar Sunartomo; Yustri Baihaqi (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2025)
This study aimed to determine the level of farmers’ motivation in cultivating jambu air Citra (Citra water apple) and to identify the factors related to their motivation. The research was conducted purposively in Sumberagung Hamlet, Tegalsari District, Banyuwangi Regency. Jambu air Citra is a commodity with high economic potential that requires optimal cultivation practices, although farmers often face obstacles such as pests and diseases that can damage or cause premature fruit drop. This research employed a descriptive quantitative approach with Rank Spearman correlation analysis. The dependent variable was farmers’ motivation, while the independent variables included age, farming experience, education level, land area, income, availability of capital, availability of production inputs, and farm location distance. The results showed that the farmers’ motivation was classified as high, with 57% or 16 farmers falling into this category. The motivation aspects, namely existence, relatedness, and growth, were all in the high category. The analysis revealed five factors significantly related to farmers’ motivation: age, farming experience, land area, income, and availability of production inputs. Meanwhile, education level, availability of capital, and distance of farm location did not show a significant relationship.